Bioactive peptides in human milk: a systematic review - Laurito, Taís Fontellas [UNIFESP] (2023)
Objectives: Identify peptides and biological activity in human milk (HM). Methodology: A systematic review was conducted in the MEDLINE, LILACS, Cochrane, Embase) and from the gray literature (Google Scholar) (CRD42020202505). until August 2020. The keywords were “human milk”, “breast milk", “breast feeding”, “mothers milk”, “lactation”, “infant milk”, “lactation”, “bioactive peptides'' and “peptides''. Two independent researchers carried out searches in the databases, selections, extractions in blind. In case of disagreement, the third author checked the eligibility criteria. The inclusion criteria were: original article, written in English, Portuguese or Spanish, which utilized human-derived milk peptide, and tested its bioactivity through in vivo or in vitro assays. Results: A total of 1519 articles were located from databases and 30 were included from references of included articles. In the end, 37 articles were included. The most common peptide activities found in HM were antimicrobial, ACE, antioxidant, immunomodulatory, opioid activities and growth regulation. The majority of studies assessed peptides from β-caseins and lactoferrin. The methodological advances were important to find a higher number of peptides, especially after the development of soft ionization methods of macromolecules applied to mass spectrometry. Conclusion: Many peptides and its bioactivities were identified in human milk. Importance of breast feeding including those bioactive peptides properties can contribute to stimulating women and society to encourage a friendly environment for breastfeeding.